2022
DOI: 10.1155/2022/8417295
|View full text |Cite
|
Sign up to set email alerts
|

Improved CenterNet for Accurate and Fast Fitting Object Detection

Abstract: Accurate and fast detection of typical fittings is the prerequisite of condition monitoring and fault diagnosis. At present, most successful fitting detectors are anchor-based, which are challenging to meet the requirements of edge deployment. In this paper, we propose a novel anchor-free method called HRM-CenterNet. Firstly, the lightweight MobileNetV3 is introduced into CenterNet to extract multi-scale features of different layers. In addition, the lightweight receptive field enhancement module is proposed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Compared with the original Faster RCNN, the improved version enhanced the accuracy of object detection [ 52 , 53 ]. In terms of fitting target detection, the HRM-CenterNet, which combined the lightweight MobileNetV3 and CenterNet, had a smaller network dimension and faster speed than the original CenterNet [ 54 ]. In [ 55 ], 15 types of vegetables were utilized to measure the effect of the DNN-framework-based recognition system on each vegetable category; in addition, the performance of learning accuracy and loss for a vegetable recognition system based on Caffe and Chainer frameworks was evaluated, which showed that the results of Caffe were better than those of Chainer.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with the original Faster RCNN, the improved version enhanced the accuracy of object detection [ 52 , 53 ]. In terms of fitting target detection, the HRM-CenterNet, which combined the lightweight MobileNetV3 and CenterNet, had a smaller network dimension and faster speed than the original CenterNet [ 54 ]. In [ 55 ], 15 types of vegetables were utilized to measure the effect of the DNN-framework-based recognition system on each vegetable category; in addition, the performance of learning accuracy and loss for a vegetable recognition system based on Caffe and Chainer frameworks was evaluated, which showed that the results of Caffe were better than those of Chainer.…”
Section: Related Workmentioning
confidence: 99%